Aspects of Community Participation in Eco-tourism: A Systematic Review - Tiwari, Shankar; Marahatta, Deepak; Devkota, Hari (Journal of Multidisciplinary Research Advancements, 2024)
Encouraging community involvement in ecotourism initiatives fosters a sense of local ownership and responsibility, which are crucial for ecotourism's lasting success and sustainability. This long-term environmental stewardship is vital for ensuring the preservation and protection of natural resources and promoting responsible tourism practices. This study comprehensively analyzes the significance of community participation in ecotourism. The study explores the types, roles, and challenges of community participation in ecotourism. Through a systematic review, the literature is collected mainly from the Scopus database, Science Direct, and Google Scholar, which were published after 2005. By following four steps of conducting thematic analysis: searching, selecting, extracting, and synthesizing, 53 articles were selected as per selection criteria. The findings highlight the diverse array of community participation, ranging from active to passive, including the role of participation of women in ecotourism. It further identified the role of community participation in economic, socio-cultural, and environmental aspects and explored possible challenges of ecotourism. The possible challenges of community participation in ecotourism, such as disparities of benefits sharing, lack of sufficient cooperation among the stakeholders, and lack of community involvement in different activities, underline the urgent need to develop comprehensive strategies to address these issues. Recommendations for future research advocate for comparative studies across diverse regions, longitudinal research, and deeper explorations of power dynamics within communities to inform more equitable and sustainable ecotourism practices.